Meningkatkan Hasil Belajar pada Materi Menegakkan Keadilan melalui Model PBL Fase C Siswa Kelas VI SDI Laja, Manggarai - Ferdinandus Tarung; Nerita Setiyaningtiyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This Classroom Action Research focuses on efforts to improve the learning outcomes of grade VI students in the subject of Catholic Religious Education and Budi Pekerti at Inpres Laja Elementary School. During the 2024/2025 school year, this research was conducted by applying a problem-based learning (PBL) model. The main objective of this study was to measure the extent to which the application of PBL can improve students' understanding of the subject matter. In addition, this study also aimed to analyze changes in student and teacher learning activities during the learning process. The results showed significant improvements in various aspects of learning. Student learning outcomes increased drastically from 64.28% in cycle I to 100% in cycle II, indicating that all students had achieved learning completeness. In addition, students' activities in participating in learning also increased from 70.83% to 87.5%, as well as teacher activities which increased from 75% to 91.66%. This increase indicates that PBL has created a more active and interactive learning environment, so that students are more involved in the learning process. Based on these findings, it can be concluded that the application of the PBL model is an effective strategy in improving the quality of learning Catholic Religious Education and Budi Pekerti in elementary schools.